2014
DOI: 10.1371/journal.pone.0111527
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Guidance for Radial Artery Catheterization: An Updated Meta-Analysis of Randomized Controlled Trials

Abstract: BackgroundSince a previous meta-analysis reported that ultrasound guidance was associated with a higher first-attempt success rate in catheterization of the radial artery, a number of randomized controlled trials (RCTs) have reported inconsistent results. The aim of the present study is to conduct an updated meta-analysis to clarify the role of ultrasound guidance for radial artery catheterization.MethodsA systematic literature search of PubMed, Embase, and Cochrane Central Register of Controlled Trials was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
40
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 22 publications
1
40
0
1
Order By: Relevance
“…17 In 2014, two systematic reviews/meta-analyses of randomized controlled trials dedicated to US-guided radial artery catheterization were published. 18,19 While both concluded that US use is associated with improved first-attempt success, a small underlying evidence base continued, and a majority of the included trials were dedicated to pediatric patients. Until 2014, there were only three included trials on adult patients; two were conducted in an emergency department setting, 14,20 and one was performed in the operating room setting.…”
mentioning
confidence: 99%
“…17 In 2014, two systematic reviews/meta-analyses of randomized controlled trials dedicated to US-guided radial artery catheterization were published. 18,19 While both concluded that US use is associated with improved first-attempt success, a small underlying evidence base continued, and a majority of the included trials were dedicated to pediatric patients. Until 2014, there were only three included trials on adult patients; two were conducted in an emergency department setting, 14,20 and one was performed in the operating room setting.…”
mentioning
confidence: 99%
“…Five meta-analyses of US guidance for radial artery catheterization in children and in adults reported a significant reduction of first-attempt failure, procedural time, and local hematoma rate compared to the standard landmark and palpation-based approach [45][46][47][48][49]. Regarding transradial access for cardiac catheterisation, a significant improvement of first-pass access rates, number of attempts and time to access in comparison to the traditional palpation-guided approach was shown in a prospective multicentre randomized control trial (RCT) [50].…”
Section: Radial Artery Anatomymentioning
confidence: 99%
“…For all subjects, ultrasound was associated with a risk ratio of 1.47 for first-attempt success; for adult subjects, the risk ratio was 1.38, and for pediatric subjects, the risk ratio was 1.73. 13 In another recent meta-analysis, Tang et al 14 also assessed first-attempt success rate and found a risk ratio of 1.98 versus 1.38 for experienced versus inexperienced operators. They concluded that ultrasound guidance reduced the mean number of attempts required for successful catheter placement, reduced time to successful catheter placement, and reduced the number of hematomas.…”
Section: Radial Artery Cannulationmentioning
confidence: 99%
“…16 Ultrasound guidance may reduce catheter-related infections due to a reduction in attempts and increased firstattempt success rate. 13,14 Ultrasound guidance reduces the likelihood of hitting the nerve bundle and other structures near the artery due to real-time visualization of the needle as it approaches the artery and underlying structures. This should reduce the morbidity associated with radial artery catheter placement because the procedure can be associated with significant pain, especially when catheter placement requires multiple attempts.…”
Section: Radial Artery Cannulationmentioning
confidence: 99%
See 1 more Smart Citation